Surveillance of multidrug-resistant organisms in a tertiary care hospital in Pakistan - Ibrahim, Saira (Infectious Diseases Journal of Pakistan, 2022)
Objective: To describe different trends of multi-drug resistant infections in a specialized consultative care hospital in Islamabad, Pakistan. Study design: Descriptive study was performed at Shifa International Hospital, during January 2015 till June 2015 Methods: Patient’s history, culture reports, and medical records were reviewed during ID consultations and data analysis was done with SPSS17. Results: A total of 300 cases in six-month period were analyzed. Eighty percent were monomicrobial. The highest percentage of infections were caused by organisms like ESBL E. Coli (23.3%). Methicillin resistant staphylococcus aureus (15.7%), Klebsiella (13.3%), Acinetobacter (13%), Enterobacter species (10.0), Pseudomonas (9.7%), Vancomycin resistant enterococci (5.3%). MSSA (3.3%) Candida species (4.7 %), and Serratia (1.7%). Conclusion: In this study we found a large proportion of drug resistant infections in Pakistan